A Pilot Phase 1 Study of Intrathecal Pemetrexed for Refractory Leptomeningeal Metastases From Non-small-cell Lung Cancer - Pan, Zhenyu; Yang, Guozi; Cui, Jiuwei; Li, Wei; Li, Yu; Gao, Pengxiang; Jiang, Tongchao; Sun, Yanan; Dong, Lihua; Song, Yuanyuan; Zhao, Gang (Frontiers in Oncology, 2019)
Objectives: We aim to determine the feasibility, safety, maximally tolerated dose (MTD), recommended dose and potential anti-tumor activity of intrathecal pemetrexed (IP). Materials and Methods: Lung adenocarcinoma patients with recurrent or progressive leptomeningeal metastases (LM) after intrathecal chemotherapy were recruited. IP dose was escalated from 10 mg. A minimum of three patients and a maximum of six were enrolled in each cohort. Schedule protocol was IP twice per week for 2 weeks in induction therapy, followed by once per week for 4 weeks in consolidation therapy. Serial samples of plasma and cerebrospinal fluid (CSF) were obtained for pharmacokinetic studies. Results: Thirteen patients were enrolled between March 2017 and July 2018. EGFR driver oncogene was identified in most of the patients. Severe adverse events (AEs) were encountered in 31% (4/13) of the cases, including myelosuppression, radiculitis, and elevation of hepatic aminotransferases (EHA). Study protocol was revised due to lethal myelosuppression. Following protocol revision, vitamin B12 and folic acid supplementation was given at the beginning of treatment, and myelosuppression was well-controlled. Dose-limiting toxicities (DLT) were myelosuppression, radiculitis, and EHA. Two patients (2/2) developed dose-limiting myelosuppression at 15 mg level. One patient (1/6) experienced dose-limiting radiculitis and EHA at 10 mg level. MTD was 10 mg. Response rate was 31% (4/13) and disease control rate was 54% (7/13). The drug concentration showed a decreasing trend in serial CSF samples following each IP. After IP, the peak plasma concentration was reached at 4 h in two cases, 6 h in two cases, 9 h in one case, and 12 h in one case, respectively. Conclusion: Pemetrexed was appropriate for intrathecal administration. IP at 10 mg dose in combination with vitamin supplementation on the schedule of 1–2 times per week showed controllable toxicity and good efficacy. This regimen paves the way for subsequent clinical trial. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT03101579.